2018
DOI: 10.1111/bph.14168
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids in arterial, pulmonary and portal hypertension – mechanisms of action and potential therapeutic significance

Abstract: The endocannabinoid system is overactivated in arterial, pulmonary and portal hypertension. In this paper, we present limited clinical data concerning the role of cannabinoids in human hypertension including polymorphism of endocannabinoid system components. We underline differences between the acute cannabinoid administration and their potential hypotensive effect after chronic application in experimental hypertension. We discuss pleiotropic effects of cannabinoids on the cardiovascular system mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 74 publications
0
37
0
3
Order By: Relevance
“…The endocannabinoid system is overactivated in hypertension [63]. Chronic CBD administration failed to modify the densities of cannabinoid and cannabinoid-like receptors (the only exception was the decrease in cardiac GPR55 levels in SHR) but decreased cardiac levels of 2-AG, OEA, DEA and DGLEA in DOCA and plasma levels of AEA and LEA in DOCA and of SEA, HEA and DGLEA in SHR.…”
Section: Effect Of Chronic Cbd In Hypertensive Animalsmentioning
confidence: 94%
See 1 more Smart Citation
“…The endocannabinoid system is overactivated in hypertension [63]. Chronic CBD administration failed to modify the densities of cannabinoid and cannabinoid-like receptors (the only exception was the decrease in cardiac GPR55 levels in SHR) but decreased cardiac levels of 2-AG, OEA, DEA and DGLEA in DOCA and plasma levels of AEA and LEA in DOCA and of SEA, HEA and DGLEA in SHR.…”
Section: Effect Of Chronic Cbd In Hypertensive Animalsmentioning
confidence: 94%
“…The possibility has to be considered that a model of hypertension connected with changes in the renin-angiotensin-aldosterone system (RAAS) (the activity of which is modified by the endocannabinoid system) might have revealed a blood pressure-lowering effect of CBD. Interestingly, opposite effects of a CB 1 receptor antagonist have been found in the cardiovascular system of SHR and of rats with a RAAS-dependent hypertension (for review, see [63]). (4) There are gender-specific differences in hypertension [17,68] and it would be interesting to extend our experiments to female rats.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…The ECS control of blood pressure (BP) involves various neuronal and non-neuronal mechanisms. Based on various human and animal studies, CB1 is suggested to play a major role in these actions and while central activation of CB1 increases BP, peripheral activation tends to lower BP [246,247]. However, the activation of either or both CBRs was demonstrated to increase contractility in vascular smooth muscles in vitro [248].…”
Section: Hypertensionmentioning
confidence: 99%
“…Cannabinoids, acting peripherally, are generally known to decrease BP. However, the final outcome depends on the type of a cannabinoid ligand, model of hypertension as well as age and sex [247]. For instance, AEA (5 mg/kg/week) decreased BP and reversed all altered cardiovascular markers and parameters in hypertensive rats [249].…”
Section: Hypertensionmentioning
confidence: 99%
“…There are reviews on more translational aspects of cannabinoids. Burkhard Hinz and Robert Ramer describe anti-tumour actions of cannabinoids (Hinz & Ramer, 2019), while Barbara Malinowska and colleagues look at the mechanisms of action and potential therapeutic significance of cannabinoids in different aspects of hypertension (Malinowska, Toczek, Pedzinska-Betiuk, & Schlicker, 2019). Kasia Starowicz (Malek & Starowicz, 2019) and Dave Finn (Okine, Gaspar, & Finn, 2019), with their respective colleagues, describe aspects of cannabinoids in joint repair problems and targetting non-canonical pathways in pain.…”
mentioning
confidence: 99%